EL NINO, LA NINA, DAN PENAWARAN PANGAN DI JAWA, INDONESIA - Arini Wahyu Utami; Jamhari Jamhari; Suhatmini Hardyastuti (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2011)
Paddy and maize are two important food crops in Indonesia and mainly produced in Java Island. This research aimed to know the impact of El Nino and La Nina on paddy and maize farmer’s supply in Java. Cross sectional data from four provinces in Java was combined with time series data during 1987-2006. Paddy supply was estimated using log model, while maize supply used autoregressive model; each was estimated using two types of regression function. First, it included dummy variable of El Nino and La Nina to know their influence into paddy and maize supply. Second, Southern Oscillation Index was used to analyze the supply changing when El Nino or La Nina occur. The result showed that El Nino and La Nina did not influence paddy supply, while La Nina influenced maize supply in Java. Maize supply increased when La Nina occurred.